2009
DOI: 10.1055/s-0029-1210764
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipoprotein Changes in Female Rats Treated with Progesterone or Synthetic Gestagens Alone or in Combination with Estradiol. I. Total and Fractionated Cholesterol and Lipoprotein Pattern

Abstract: In adult female rats, the effects of progesterone (P), norethisterone acetate (NEA), levonorgestrel (LNG), dienogest (DEG) and chlormadinone acetate (CMA) given alone at doses of 2.5 or 10 mg/kg p.o. or in combination with s.c. implanted estradiol (E2) on total cholesterol (TC), high-density-lipoprotein cholesterol (HDL-C), low-density-lipoprotein cholesterol (LDL-C) and very-low-density-lipoprotein cholesterol (VLDL-C) were investigated. Additionally, the lipoprotein pattern was determined using agarose gel e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In a previous study in rats was shown that pregnane derived gestagens such as chiormadinone acetate or progesterone differ from 19-norgestagens by the lack of both the serum cholesterol lowering and its corresponding estradiol antagonizing activities (Tkocz et al, 1985;Tkocz et al, 1988). In this paper the modulating influence of these two types of gestagens on the triglyceride (TG) metabolism of female rats is discussed.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In a previous study in rats was shown that pregnane derived gestagens such as chiormadinone acetate or progesterone differ from 19-norgestagens by the lack of both the serum cholesterol lowering and its corresponding estradiol antagonizing activities (Tkocz et al, 1985;Tkocz et al, 1988). In this paper the modulating influence of these two types of gestagens on the triglyceride (TG) metabolism of female rats is discussed.…”
Section: Introductionmentioning
confidence: 84%
“…E2 was given as implant or in an aqueous vehicle (2% ethanol: tylose). Further details see (Tkocz et al, 1988).…”
Section: Materials Ami Methodsmentioning
confidence: 99%
See 1 more Smart Citation